Bentuk Pemerintahan dalam Pandangan Aristoteles - Fadil, Muhammad (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2012)
It’s rather difference than Plato’s political idea, Aristotle expanded his political views into more scientific models. He elaborated the ideas of democracy, oligarchy, tyranny, and more which are becoming fundamental to basic knowledge of political studies. In spite of its classiness, Aristotle had put great contributions to basic political studies. All students studying politic need to see this philosophical aspect of politic and government.